Introduction. Applications of artificial intelligence in various areas of social, media, cultural, political and economic life - Marsili, M.; Wróblewska-Jachna, J. (Media i Społeczeństwo, 2024)
This bilingual special issue of (Media and Society) devoted to the challenges that the rising of artificial intelligence poses to contemporary societies provides the readership with a broad overlook over issues that are dominating the political and public debate and that will still be over the table in the next years. The contributions included in the publication, which is meant to be a cornerstone for sociologists, social psychologists, political scientists, media experts, legal scholars, and practitioners, are largely drawn from the annual international scientific media conference organized at the University of Bielsko-Biała (Poland